2003
DOI: 10.1097/01.sap.0000041480.89609.79
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dermoids: Three Cases and a Modified Treatment Algorithm

Abstract: Congenital orbitofacial dermoids can be segregated into frontotemporal, orbital, and nasoglabellar regions. Although 10% to 45% of nasoglabellar dermoids present with sinus tracts and occasional intracranial extension, it is rare for frontotemporal dermoids to do so. Frontotemporal dermoids typically manifest as superficial, slow-growing masses that are treated by simple excision. In this retrospective review of 24 patients with congenital orbitofacial dermoids, the authors noted three cases of temporal dermoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…While midline dermoids are not infrequently found to invade the cranium, there are fewer than 20 case reports which describe lateral frontotemporal dermoids with associated sinus tracts and bony invasion, of which 7 have extended intracranially [1,2,5,7,8,9,10,11,12,13,14,15]. Intradiploic dermoids represent between 0.04 and 0.7% of all cranial tumors [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While midline dermoids are not infrequently found to invade the cranium, there are fewer than 20 case reports which describe lateral frontotemporal dermoids with associated sinus tracts and bony invasion, of which 7 have extended intracranially [1,2,5,7,8,9,10,11,12,13,14,15]. Intradiploic dermoids represent between 0.04 and 0.7% of all cranial tumors [17].…”
Section: Discussionmentioning
confidence: 99%
“…They may appear as a lytic defect in the skull, giving a wide differential diagnosis by imaging alone. Frontotemporal dermoid cysts associated with sinus tracts or bony invasion are extremely rare, with only 20 case reports described in the literature [1,2,5,7,8,9,10,11,12,13,14,15]. We present a report of a rare intradiploic frontotemporal dermoid, without soft tissue extension, in the cranium of a 2-year-old male.…”
Section: Introductionmentioning
confidence: 96%
“…5,10 Regardless of the inability to predict extension of the lesion or the risk of infection based on physical examination alone, the recommendation for preoperative imaging of these lesions is also inconsistent among reports. 4,7,8 Although intracranial involvement has been reported, we were unable to identify any reports of intradural extension in the literature, and excision in the absence of imaging has been described, with good results. Nevertheless, we still believe that MRI and CT scanning allow one to quantify the extent of inflammation, and to identify the presence of osseous involvement, intracranial extension, and/ or orbital extension.…”
Section: Discussionmentioning
confidence: 93%
“…Unfortunately, these findings alone do not appear to be predictive of intracranial extension. 1,[4][5][6][7][8][9][10] When considering infection, there have been no reported cases of meningitis associated with frontotemporal pits, regardless of intracranial involvement. In contrast, reports of orbital infections occurring in concert with the sinus tract are described.…”
Section: Discussionmentioning
confidence: 99%
“…The tracts are not usually to the eyelids, but when they do occur, the sinus tract opening is typically situated in the frontotemporal or orbitotemporal region. Lacey et al 16 reported 3 cases of orbitotemporal dermoids with a sinus tract and bone invasion. When a sinus tract is present, recurrent infections or intermittent discharge of sebaceous material is common.…”
Section: Discussionmentioning
confidence: 99%